Pediatric Beta-Thalassemia Major: Chronic Transfusion, Oxidative Stress, and the Overlooked Surgical Burden - Junaid Ahmed, Tahir Shahzad Nawaz Babar, Tabassum Bashir, Abid Ali Ranjha, Hamza Sohail, Azal Jodat (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Association between chronic transfusion therapy, oxidative stress biomarkers, and surgicalinterventions in pediatric patients with beta-thalassemia major was evaluated in a prospectivecohort of 200 children aged 5–16 years receiving regular transfusions and chelation therapy. Serummarkers including malondialdehyde